[18F]FDG PET/MRI enables early chemotherapy response prediction in pancreatic ductal adenocarcinoma - Harder, Felix N.; Jungmann, Friederike; Kaissis, Georgios A.; Lohoefer, Fabian K.; Ziegelmayer, Sebastian; Havel, Daniel; Quante, Michael; Reichert, Maximillian; Schmid, Roland M.; Demir, Ihsan Ekin; Friess, Helmut; Wildgruber, Moritz; et al. (EJNMMI Research, 2021)
Purpose: In this prospective exploratory study, we evaluated the feasibility of [18F]fluorodeoxyglucose ([18F]FDG) PET/MRI-based chemotherapy response prediction in pancreatic ductal adenocarcinoma at two weeks upon therapy onset. Material and methods: In a mixed cohort, seventeen patients treated with chemotherapy in neoadjuvant or palliative intent were enrolled. All patients were imaged by [18F]FDG PET/MRI before and two weeks after onset of chemotherapy. Response per RECIST1.1 was then assessed at 3 months [18F]FDG PET/MRI-derived parameters (MTV50%, TLG50%, MTV2.5, TLG2.5, SUVmax, SUVpeak, ADCmax, ADCmean and ADCmin) were assessed, using multiple t-test, Man–Whitney-U test and Fisher’s exact test for binary features. Results: At 72 ± 43 days, twelve patients were classified as responders and five patients as non-responders. An increase in ∆MTV50% and ∆ADC (≥ 20% and 15%, respectively) and a decrease in ∆TLG50% (≤ 20%) at 2 weeks after chemotherapy onset enabled prediction of responders and non-responders, respectively. Parameter combinations (∆TLG50% and ∆ADCmax or ∆MTV50% and ∆ADCmax) further improved discrimination. Conclusion: Multiparametric [18F]FDG PET/MRI-derived parameters, in particular indicators of a change in tumor glycolysis and cellularity, may enable very early chemotherapy response prediction. Further prospective studies in larger patient cohorts are recommended to their clinical impact.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Chemotherapy; PDAC; PET/MRI; Response prediction